Ambiguity in the Kalām Cosmological Argument: Exposing the Limits of First-Order Predicate Logic - Ahsan, Abbas ca. 20./21. Jh. (Sophia, 2025)
In this paper, I apply Graham Priest’s logical critique of the cosmological argument to the Kalām Cosmological Argument (KCA), focusing on a key ambiguity in its first premise: "Whatever begins to exist has a cause." When formalized in first-order predicate logic (FOL), this premise admits two non-equivalent interpretations. One of which allows for multiple distinct causes while another posits a single universal cause. This logical ambiguity reveals a limitation of FOL in expressing metaphysical claims with the necessary precision. By extension, this ambiguity undermines the structural coherence of the KCA when expressed in FOL. My central aim is not to refute the KCA’s conclusion but to demonstrate that its first-order formulation lacks logical determinacy. To address this, I develop a second-order modal logical (SOML) framework that incorporates functional mappings, uniqueness constraints, and metaphysical necessity. This revised formalism eliminates the ambiguity while preserving the KCA’s philosophical commitments.